Biological Response to Carbon-Family Nanomaterials: Interactions at the Nano-Bio Interface - Rahmati, Maryam (Front Bioeng Biotechnol, 2019)
During the last few decades, several studies have suggested that carbon-based nanomaterials, owing to their unique properties, could act as promising candidates in biomedical engineering application. Wide-ranging research efforts have investigated the cellular and molecular responses to carbon-based nanomaterials at the nano-bio interfaces. In addition, a number of surface functionalization strategies have been introduced to improve their safety profile in the biological environment. The present review discusses the general principles of immunological responses to nanomaterials. Then, it explains essential physico-chemical properties of carbon-familynanomaterials, including carbon nanotubes (CNTs), graphene, fullerene, carbon quantum dots (CDs), diamond-like carbon (DLC), and mesoporous carbon biomaterials (MCNs), which significantly affect the immunological cellular and molecular responses at the nano-bio interface. The discussions also briefly highlight the recent studies that critically investigated the cellular and molecular responses to various carbon-based nanomaterials. It is expected that the most recent perspective strategies for improving the biological responses to carbon-based nanomaterials can revolutionize their functions in emerging biological applications.